Mathematics anxiety and mathematics motivation among students in the faculty of science of a public university in Malaysia - Mohammad Ali, Nuur Adila; Che Hassan, Norlizah (Human Resource Management Academic Research Society, 2019)
Mathematics anxiety and Mathematics motivation has been the target of most psychological and educational research in the past few years. Many studies showed that math anxiety and math motivation is an influence on students’ achievement in school. In fact, the performance of students especially in Math are weak not only in secondary school but in university level as well, even though they have spent almost eleven years in formal education system. The aims of this study is to identify the differences on math anxiety and math motivation based on gender and to investigate the relationship between math anxiety and math motivation among students in the faculty of science of a public university in Malaysia. The sample consisted of 104 (23 male and 81 female) undergraduate students in the Faculty of Science. The instruments used to measure the math anxiety level and math motivation are Mathematics Anxiety Rating Scale (MARS) and The Motivated Strategies for Learning Questionnaire (MSLQ). The Alpha Cronbach scored based on the pilot test shown the score value of Math anxiety is 0.87 and Math Motivation 0.85. The data were analyzed using Pearson correlation and independent-samples t- tests (SPSS 11.5). The results showed a significant moderate correlation between math anxiety and math motivation. It is also revealed that there were significant gender differences between male and female in math anxiety and math motivation. Hence, the findings may help in better understanding of mathematics-learning processes and provide important insights for intervention or remedial programs that targeting in improving mathematics-learning process of the students.